Folklore and social media - Peck, Andrew, editor; Blank, Trevor J., editor; Utah State University Press, publisher (Colorado State University. Libraries, 2020)
New scholarship to study digital folklore. A unique virtual, hybridized platform for human communication, social media is more dynamic, ubiquitous, and nuanced than the internet ever was by itself. Taking both the "digital" and "folklore" elements seriously because social media fundamentally changes folk practices in new and often invisible ways.--Provided by publisher.
Introduction: old practices, new media / Andrew Peck -- #LatinxGradCaps, cultural citizenship, and the "American dream" / Sheila Bock -- Bridges, sex slaves, Tweets and guns: a multi-domain model of conspiracy theory / Timothy R. Tangherlini, Vwani Roychowdhury, and Peter M. Broadwell -- The vernacular vortex: analyzing the endless churn of Donald Trump's Twitter orbit / Whitney Phillips and Ryan M. Milner -- The death of Doge: institutional appropriations of the Internet memes / Andrew Peck -- "Zero is our quota": folkloric narratives of the other in online forum comments / Liisi Laineste -- Trickster remakes this White House: booby traps and bawdy/body humor in post-election prankster Biden memes / Jeana Jorgensen and Linda J. Lee -- Dear David: affect and belief in Twitter horror / Kristiana Willsey -- The beauty, the beast, and the Fanon: the vernacularization of the literary canon and an epilogue for modernity / Tok Thompson -- Classifying #BlackLivesMatter: genre and form in digital folklore / Lynne S. McNeill -- The clown legend cascade of 2016 / John Laudun -- The blue whale suicide challenge: hypermodern ostension on a global scale / Elizabeth Tucker -- Overt and covert aspects of virtual play / Bill Ellis.
Keywords: Folklore and the Internet; Communication in folklore; Social media; Digital media